The Importance of Pragmatics in Translating Advertising Slogans - Shokhista Aliyevna Mahkamova (Genius Journals, 2022)
Selling products is the most important goal in the world of advertising. As companies are becoming more global, they are looking for new ways to sell their products all over the world. The question arises of what to advertise. People around the world have different customs as well as different likes and dislikes. The best advertisement in the world means nothing if the product is not right for the market. This article highlights the importance of pragmatics in translating advertising slogans.
Keywords: advertisement; advertise; selling products; translation